A new species of Cyrtochilum (Orchidaceae: Oncidiinae) from the Eastern Cordillera of Colombia - Gutiérrez Morales, Nicolás (Universidad de Costa Rica, 2018)
A new species of Cyrtochilum from the Eastern Cordillera of Colombia is described and illustrated. The new species is most similar to the pink-flowered Cyrtochilum distans but is distinguished by its white and yellow-green flowers with spreading sepals and a pink lip with a basally yellow and apically white callus consisting of two parallel keels (vs. pink lateral sepals that are fused to about half or more of their length and a white callus consisting of two basal and two apical spreading keels).